Thermal analysis of the internal climate condition of a house using a computational model - Knutsen, Christopher (Department of Mechanical Engineering, 2021)
The internal thermal climatic condition of a house is directly affected by how the building envelope (walls, windows and roof) is designed to suit the environment it is exposed to. The way in which the building envelope is constructed has a great affect on the energy required for heating and cooling to maintain human thermal comfort. Understanding how the internal climatic conditions react to the building envelope construction is therefore of great value. This study investigates how the thermal behaviour inside of a simple house reacts to changes made to the building envelope with the objective to predict how these changes will affect human thermal comfort when optimising the design of the house. A three-dimensional numerical model was created using computational fluid dynamic code (Ansys Fluent) to solve the governing equations that describe the thermal properties inside of a simple house. The geometries and thermophysical properties of the model were altered to simulate changes in the building envelope design to determine how these changes affect the internal thermal climate for both summer and winter environmental conditions. Changes that were made to the building envelope geometry and thermophysical properties include: thickness of the exterior walls, size of the window, and the walls and window glazing constant of emissivity. Results showed that there is a substantial difference in indoor temperatures, and heating and cooling patterns, between summer and winter environmental conditions. The thickness of the walls and size of the windows had a minimal effect on internal climate. It was found that the emissivity of the walls and window glazing had a significant effect on the internal climate conditions, where lowering the constant of emissivity allowed for more stable thermal conditions within the human comfort range.